Serafina and the black cloak - Beatty, Robert, 1963- (Serafina, 2015)
In 1899, a twelve-year-old rat catcher on North Carolina's Biltmore estate teams up with the estate owner's young nephew to battle a great evil and, in the process, unlocks the puzzle of her past.